Bioequivalence of Intravenous and Oral Rolapitant: Results From a Randomized, Open‐Label Pivotal Study. (14th September 2017) - Wang, Xiaodong; Zhang, Zhi‐Yi; Powers, Daniel; Wang, Jing; Lu, Sharon; Arora, Sujata; Hughes, Lorraine; Christensen, Jennifer; Kansra, Vikram
Abstract: Rolapitant, a selective and long‐acting neurokinin‐1 receptor antagonist, is approved in an oral formulation for the prevention of delayed chemotherapy‐induced nausea and vomiting in adults. The objective of this pivotal study was to assess the bioequivalence of a single intravenous infusion of rolapitant versus a single oral dose of rolapitant. In this randomized, open‐label phase 1 study, healthy volunteers were administered rolapitant as a 180‐mg oral dose or a 30‐minute 166.5‐mg intravenous infusion. Blood samples for pharmacokinetic analysis were collected predose and at points up to 912 hours postdose. Criteria for bioequivalence of the intravenous dose versus the oral dose were met if the 90% confidence intervals (CIs) for the ratios of the geometric least‐squares means (GLSMs) for the area under the plasma concentration‐time curve (AUC) from time 0 to the time of the last quantifiable concentration (AUC0–t ) and AUC from time 0 extrapolated to infinity (AUC0–∞ ) for rolapitant were within 0.80–1.25. Mean rolapitant systemic exposure and half‐lives were similar in the oral (n = 62) and intravenous (n = 61) rolapitant groups. The 90%CIs of the ratio of GLSMs were within the 0.80–1.25 range for AUC0–t (0.94–1.09) and AUC0–∞ (0.93–1.10). The incidence of treatment‐emergent adverse events, all mild or moderate in severity, was similar in the intravenous and oral groups. A 166.5‐mg intravenous infusion of rolapitant met the bioequivalence criteria based on AUC to a 180‐mg oral dose and was well tolerated.